Production Track Balance Analysis Using The Moodie Young Method - Yudi Daeng Polewangi; Sutrisno; Susilawati (International Journal of Health Engineering and Technology, 2022)
The purpose of this study was to find out the efficiency level of the production line by using the Moodie Young method. Where the method was used to determine the balance level of the production line consisted of 3 parts, namely: Line Efficiency, Balance Delay, and Smooth Index.The results showed that in the actual production line arrangement, there were 5 workstations with 7 work elements with Line Efficiency results of 40.29 %, Balance Delay of 59.70%, and Smoothness Index of 9578.22.